2017
DOI: 10.1016/j.arr.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Cutting back on the essentials: Can manipulating intake of specific amino acids modulate health and lifespan?

Abstract: With few exceptions, nutritional and dietary interventions generally impact upon both old-age quality of life and longevity. The life prolonging effects, commonly observed with dietary restriction reportedly are linked to alterations in protein intake and specifically limiting the dietary intake of certain essential amino acids. There is however a paucity of data methodically evaluating the various essential amino acids on health- and lifespan and the mechanisms involved. Rodent diets containing either lower m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 137 publications
(191 reference statements)
0
52
0
Order By: Relevance
“…Some studies examining aging‐related outcomes and longevity in rodents consuming methionine‐deficient diets have shown beneficial effects of methionine restriction on metabolic health and lifespan . It appeared that methionine restriction may itself directly activate Nrf2, and that a methionine‐restricted diet enhances the activity of antioxidant enzymes, and reduces ROS production and oxidative stress damage . In this study, we did not investigate whether the oral administration of l ‐ methionine could influence the lifespan extension.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies examining aging‐related outcomes and longevity in rodents consuming methionine‐deficient diets have shown beneficial effects of methionine restriction on metabolic health and lifespan . It appeared that methionine restriction may itself directly activate Nrf2, and that a methionine‐restricted diet enhances the activity of antioxidant enzymes, and reduces ROS production and oxidative stress damage . In this study, we did not investigate whether the oral administration of l ‐ methionine could influence the lifespan extension.…”
Section: Discussionmentioning
confidence: 86%
“…Dietary MR produces many beneficial effects on metabolic health in both rodents and humans, preventing weight gain and fat accretion, and improving control of blood glucose (10, 18, 43, 44). However, humans have significant difficulties in remaining compliant with severe dietary alterations.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which MR promotes metabolic health and longevity have been investigated at length but remain poorly understood (18). Many of the metabolic benefits of MR have been attributed to increased levels of the hormone fibroblast growth factor (Fgf)-21, which promotes hepatic insulin sensitivity and increases energy expenditure.…”
mentioning
confidence: 99%
“…Nevertheless, studies performed in a number of animal species have shown that protein restriction increases both lifespan and healthy lifespan, implying that these effects involve evolutionarily conserved mechanisms that might also be operational in humans . The positive effects on lifespan achieved using diets with low protein or amino acid content can also be achieved by reductions in specific amino acids, with substantial restriction of methionine being most effective . Moreover, this reduction in methionine levels changes the cellular metabolism and has a supportive effect in cancer treatment .…”
Section: Cr Macronutrient Restriction and Time Restricted Food Intakementioning
confidence: 99%